The cost-effectiveness of different types of educational interventions in type II diabetes mellitus: A systematic review - Wan Nur Liyana Hazwani Wan Rohimi; Nurul Ain Mohd Tahir (Frontiers Media S.A., 2022)
Aims: Educational interventions are effective to improve peoples' self-efficacy in managing diabetes complications and lifestyle changes. This systematic review aims to assess and compare various aspects of educational interventions and to provide updated pharmacoeconomics data.Methods: Literature searches were conducted using databases such as EBSCOhost, Ovid, PubMed, Scopus, and Web of Science. Outcomes such as study characteristics, costs, medication adherence, effectiveness and were narratively summarized, and the quality of each article was assessed.Results: A total of 27 studies were retrieved. The types of educational interventions were classified as face-to-face strategy, structured programs, telemedicine health education, a combination approach, and others. All types of educational interventions (N = 24, 89%) were reported to be cost-effective. The cost-effectiveness of the other two studies was considered to be not cost-effective while the outcome of one study could not be determined. The majority of the studies (N = 24, 89%) had moderate-quality evidence whereas thirteen (48%) studies were regarded to provide high-quality economic evaluations.Conclusion: All types of educational interventions are highly likely to be cost-effective. The quality of economic evaluations is moderate but the most cost-effective types of educational interventions could not be determined due to variations in the reporting and methodological conduct of the study. A high-quality approach, preferably utilizing the societal perspective over a long period, should be standardized to conduct economic evaluations for educational interventions in T2DM.Systematic Review Registration: website, identifier registration number.